Pengembangan Model Pembelajaran Snowball Throwing Berorientasi Life Skill Siswa Kelas II SD Negeri Ngadisari 1 Kabupaten Probolinggo - Romadani, Isa; Wardana, Ludfi Arya; Kasdriyanto, Didit Yulian (CV. ITTC INDONESIA, 2024)
Based on the background that has been explained, the aim of this research is to develop a Life Skill-oriented Snowball Throwing learning model for class II students at SD Negeri Ngadisari 1. This research uses the Borg and Gall development model with the first stage being research and collecting initial information, then planning and developing initial product format, then make revisions if during validation there are things that need to be improved based on input and suggestions from the validator and carry out field trials. The results of this research show that the Life Skill-oriented Snowball Throwing learning model is very good, which can be seen from the validation results from validator experts and filling out questionnaires and responses from students. Based on the validation results, media experts got 93% and can be declared very good with several suggestions. Then the material expert validation can be a percentage of 96% and can be declared very good. Meanwhile, the results of the teacher's trial got 93% and the results of the trial with students got a response of 97%.